IL-2 TUMOR TREATING FIELDS: IMPROVING THE ODDS FOR PATIENTS WITH GLIOBLASTOMA. (3rd December 2022) - Hottinger, Andreas F
Abstract: Tumor treating fields (TTFields) is a novel, noninvasive regional antimitotic treatment modality approved for use in newly diagnosed glioblastoma (GBM). Nowadays, it is an integral part of the standard management of GBM. TTFields therapy delivers intermediate frequency (100-300 kHz), low intensity (1-3 V/cm), alternating electric fields to the tumor using transducer arrays placed on the scalp. TTFields disrupt mitotic spindle formation, block cell division and disrupt intracellular constituents, inducing apoptosis, autophagy and immune mediated cell death, as well as impairment of cell migration and DNA repair. A phase III trial of TTFields therapy in combination with maintenance temozolomide has established that TTFields are associated with minimal toxicity and result in a significant improvement of progression free survival and overall survival. Importantly, it also significantly increases the percentage of long-term survivors while maintaining the quality of life of the patients. Recent work has focused on a number of key parameters to better understand which patients are most likely to benefit from this new therapeutic approach. In this presentation, we will review the basics of TTFields therapy and the available clinical evidence that justify its use in GBM. We will also discuss how to best integrate this novel therapeutic approach in the current management of patients with newly diagnosed and progressing glioblastoma, highlighting how this was performed in the Swiss Institutions. We will also review and discuss recent work that analyzed the pertinence of TTFields in specific subgroups of patients, analyze patterns of progression under TTFields and discuss ongoing translational and clinical research.